Effect of Dapagliflozin in Lowering Risk of Heart Failure Severity: Meta-Analysis - Andreza Andreza; Anis Nur Widayati (Masters Program in Public Health, 2023)
Background: Heart failure is a progressive health problem with high mortality and morbidity rates in developed as well as developing countries including Indonesia. Dapagliflozin is one of the oral antidiabetic medicines of the class of sodium-glucose cotransporter-2 (SGLT2) inhibitors, used in people with type 2 diabetes mellitus (DMT2). Unlike other oral anti-diabetes that work to stimulate insulin secretion or increase insulin sensitivity, dapagliflozin works in the kidneys by competitively inhibiting the SGLT2 protein reversibly which serves in glucose reabsorption in the glomerulus thereby lowering blood sugar levels in T2DM patients. This study aimed to determine the estimated effect of dapagliflozin on the severity of heart failure patients.Subjects and Method: This study was a systematic review and meta-analysis with PICO. Population= Heart failure patients over 18 years old. Intervention= administration of dapagliflozin. Comparison= Placebo. Outcome= severity of Heart Failure. The articles used PRISMA flowchart guidelines. The article search process was conducted from 2019 to 2022 using databases from PubMed, Google Scholar, and Scopus with the search keywords Dapagliflozin, Heart Failure, and Placebo. The analysis was performed using RevMan 5.4 software.Results: A total of 8 articles from across 2 continents, America and Asia, reviewed in the meta-analysis, showed that administering Dapagliflozin could reduce the risk of heart failure severity by 0.99 units compared to without dapagliflozin, however, it was statistically insignificant (OR= 0.99; 95% CI= 0.92 to 1.06; p= 0.710).Conclusion: The administration of Dapagliflozin lowers the risk of heart failure severity and is statistically significant. Keywords: dapagliflozin, heart failure, placebo Correspondence: Andreza. Universitas Hasanuddin. Jl. Perintis Kemerdekaan No.KM.10, Tamalanrea Indah, Kec. Tamalanrea, Makasar City, South Sulawesi. Email: andrezafauzialghifary@gmail.com. Mobile: +625299015320.